Amyloid-Associated Alopecia: A Reappraisal Including Its Pathophysiology. (November 2019) - Magro, Cynthia M.; Solomon, Garron J.; Kendrick, Mary Jo J.; Momtahen, Shabnam
Abstract : Abstract: Primary systemic amyloidosis has a varied clinical presentation, making it one of the great masqueraders of other disease entities in clinical medicine. The association of amyloidosis with alopecia is uncommon with at least 22 cases reported in the literature mostly in the setting of systemic amyloidosis. Alopecia in these patients occurs either as the initial presentation of the systemic amyloidosis or it happens during the disease course. The occurrence of amyloid alopecia associated with light chain (LC) restricted plasmacytic infiltrates in the absence of systemic amyloidosis, however, it is not well known. We report 3 cases of LC-associated amyloidosis presenting with alopecia, whereby there was evidence of a systemic plasma cell dyscrasia in 2 of the patients, one of whom developed multiple myeloma. None of the patients had systemic amyloidosis. Skin presentation in the patient with multiple myeloma was characterized by a diffuse form of alopecia affecting the entire scalp, eyebrow, and axillary and pubic hair in contrast to the localized form of alopecia noted in the other 2 patients. The mechanism by which LC-associated amyloidosis eventuates in this pattern of nonscarring alopecia potentially reflects the affinity of this form of amyloid for dermatan sulfate. Dermatan sulfate is found at highest concentrations within the adventitial dermis of the superficial to mid isthmic portions of the anagen hair follicles likely interfering with the hair cycle and induces early hair follicle involution. The result is a pattern of alopecia that can clinically and to some extent pathologically resemble either androgenetic alopecia or alopecia areata.